PRINCIPLES OF FORMATION OF RESEARCH AND EDUCATIONAL OBJECTS OF INNOVATIVE PURPOSE - Pozdnyakov, Andrey; Pozdnyakova, Ekaterina; Marmolejo, Carlos (Journal of Applied Engineering Science, 2020)
An analysis of global trends in the development of education and science shows that a modern university has ceased to be a place for transferring knowledge from a teacher to a student in the form of lectures. Today, the university fulfills the task of forming intelligence in the form of knowledge, innovation, competencies, being at the same time a space for researchers, teachers, and students to meet and work together. This article discusses the main functional components of modern Research and Educational objects. The analysis revealed a common unifying link in the relationship of these blocks. The result of studying domestic and foreign experience in the design and construction of educational centers was the identification of the basic principles of their formation.